ICU handover procedure: the Greek perspective - Aslanidis, Theodoros; Kontos, Athanasios; Chytas, Ilias; Peftoulidou, Maria Giannakou (International Journal of Research in Medical Sciences, 2017)
Background: Passing the right information poses a challenge in clinical practice. This is the first study in Greece that tries to describe the handover procedure in an intensive care unit to a tertiary hospital. Methods: A two phase study was conducted during a 155 days period. It included a blind and open observational study which examined the quality and content of clinical handover by night shift doctor to the medical team and a survey about the process. Retrospective cross-checking of the information handed over with one written down in the actual patient record was also conducted. Results: A total of 800 set of patients’ daily records were examined. A structure of system-based approach of the handover was recorded, with system coverage varying from 21% (nutrition) to 86% (respiratory system) and good relation with the actual record in most areas of interest. Other areas, such as comorbidities, and relatives’ issue were poorly covered. Education meeting that was held between the two phases did ameliorate the content and the quality of information passed over, and in some areas, proved to have a positive effect on certain aspect of handover like e.g. frequency of interruptions, infection status, relatives’ issues and proposed management plan coverage. Conclusions:Handoverprocess is vital for maintaining stability and quality of care in intensive care unit. Its continual efficiency reevaluation is at least as important as the handover itself for preserving it as a valuable tool in everyday practice.